Lúcio Cardoso, Maleita e Pirapora. Historicidade e cultura popular na obra de Lúcio Cardoso - Zanoni Neves (Confins)
In the novel Maleita, Lucio Cardoso used his father's memories about the history of Pirapora (Minas Gerais) in the last decade of the nineteenth century. The town then developed with the construction of a tissue deposit owned by a company known today as Companhia de Tecidos Cedro e Cachoeira. But the novel is also illustrated with a description of the regional types (native), immigrants, elements of popular culture and belief system, without losing sight of the local government, the riverside landscape and the momentum created by transport integrating the municipality into the regional economic system. We confronted the plot of the novel with information provided by a research held in the region, interpreting it with the contribution of concepts of social anthropology without forgetting the contribution of the history of literature.